Цінністно-орієнтоване управління проектами альтернативної енергетики - Возний, Олександр Михайлович; Борисова, Наталія Ігорівна (НТУ "ХПІ", 2017)
Пропонується ціннісно-орієнтований підхід до управління проектами альтернативної енергетики, в основу якого покладені: класифікація етапів життєвого циклу продуктів ПАЕ, адаптована під цілі і завдання інформаційного моделювання; класифікація проектів альтернативної енергетики та фаз їх життєвих циклів; класифікація зацікавлених сторін та їх цінностей; механізм оцінки цінностей на різних фазах життєвого циклу; цінністно-орієнтоване управління ризиками. Управління цінністю викладене з позицій утилітарного підходу.

The value-oriented approach to project management of renewable energy based on classification stage of the life cycle of products of the projects, adapted to the goals and objectives of information modeling, which allowed to formulate stricter requirements information models used at different stages of power plant is proposed. A classification of the alternative energy projects, which highlighting areas for activities is proposed. The list of stakeholders that have an impact on alternative energy projects and presented their classification is defined. The value of alternative energy projects considered from the standpoint of a utilitarian approach, using the concept of utility and on the basis of this concept proposed classification values of alternative energy projects. Criteria values as indicators for assessing the value of alternative energy projects and their weights determined by pairwise comparison. To take into account the changes of the value criteria over time proposed to use the key control points value, assessed value criteria in various key points of control, defined indicator of total value of alternative energy projects. The classification of risks and tools for value-oriented risk management in alternative energy projects is proposed. Further study authors plan to link the development of mechanisms for harmonization value alternative energy projects for their stakeholders.
Values-oriented project management of renewable energy
Keywords: альтернативна енергетика; управління проектами; оцінка цінності; стейкхолдери; життєвий цикл; ризики; alternative energy; project management; evaluation values; stakeholders; lifetime risks